HUBUNGAN KAUSAL ANTARA LITERASI KEUANGAN, FAKTOR DEMOGRAFI, PERILAKU KEUANGAN, DAN KEPUTUSAN INVESTASI - Ratnasari, Desi; Sadeli, Sadeli; Sugiarto, Meilan; Fadma Tj, Rosalia Dwi (Jurnal Paradigma, 2024)
The focus of this study is to analyze the effect of financial literacy and demographic factors on financial behavior and its impact on investment decisions. This study uses a quantitative approach, where the influence between research variables is analyze with Warp PLS. Data collection instruments use questionnaires that are distributed online using google form. The study population is members of the beginner stock investor community in the Yogyakarta region. Purposive sampling is use to determine population members who can be research samples. The number of samples used was 86 people. Based on the results of research shows that financial literacy and demographic factors have a positive and significant impact on financial behavior, as well as investment decisions. Furthermore, financial behavior has a positive and significant impact on investment decisions. Financial literacy and demographic factors when mediated by financial behavior have a positive but insignificant effect on investment decisions. The results of this study indicate an increase in financial literacy, maturity in the demographic factors of novice stock investors, and with good financial behavior can directly determine investment decisions. Subsequent research can consider the impact of investment risks or reference groups on financial behavior and investment decisions.